Importance of Expanding Midwifery-led Units and Midwifery Care in Reducing Maternal Deaths in Nepal - Mahato, Preeti; Teijlingen , Edwin van (Europasian Journal of Medical Sciences, 2024)
It is important to collect good quality routine data to assess the quality and functioning of any health system. In the recent past, the challenge with assessing the quality of Nepal’s maternity services has partly been due to the absence of appropriate data sets. The Nepal Demographic and Health Surveys (DHSs), conducted every five years or so, have been the best possible data source to make comparisons over time.1 The recently (2022) published Nepal Maternal Mortality Study (NMMS) is the first integrated national effort by the Government of Nepal to estimate the country’s maternal mortality ratio (MMR) and the causes of maternal morbidity and mortaltiy.2 This study collected data on live births and deaths of women of reproductive age, for the last 12 months preceding the 2022 national census. The NMMS identified 622 maternal deaths from November 2020 to November 2021, however the detailed analysis is limited to 611 cases (due to missing information). According to the NMMS, Nepal’s MMR was 151 per 100,000 live births in 2021. The majority of maternal deaths (57%) occurred in health facilities, and a further 17% died on the way to a health facility. Of most of the women who died during childbirth and in the post-partum period (i.e., not during pregnancy), 76% gave birth at a health facility.2 Out of the women who died at a health facility, the majority (62%) gave birth at a government institution. About half (46%) of births among the deceased women were assisted by a doctor. Yet, only one-fifth (19%) were attended by a staff nurse or midwife, and 10% were attended by an auxiliary nurse midwife (ANM). Among the women who died, 56% had a vaginal delivery and 38% had a caesarean section.